Novel Catabolic Pathway of Quercetin-3-O-Rutinose-7-O-α-L-Rhamnoside by Lactobacillus plantarum GDMCC 1.140: The Direct Fission of C-Ring - Huang, Guitao; Lai, Mingwen; Xu, Canhua; He, Shan; Dong, Lihong; Huang, Fei; Zhang, Ruifen; Young, David James; Liu, Hesheng; Su, Dongxiao (Frontiers in Nutrition, 2022)
Lychee pulp phenolics (LPP) is mainly catabolized in the host colon, increasing the abundances of Bacteroides and Lactobacillus. Herein, five selected gut microbial strains (Bacteroides uniformis, B. thetaiotaomicron, Lactobacillus rhamnosus, L. plantarum and L. acidophilus) were separately incubated with LPP to ascertain the specific strains participating in phenolic metabolism and the corresponding metabolites. The results indicated that B. uniformis, L. rhamnosus and L. plantarum were involved in LPP utilization, contributing to 52.37%, 28.33% and 45.11% of LPP degradation after 48h fermentation, respectively. Unprecedentedly, the metabolic pathway of the major phenolic compound quercetin-3-O-rutinose-7-O-α-L-rhamnoside by L. plantarum, appeared to be the direct fission of C-ring at C2-O1 and C3-C4 bonds, which was proved from the occurrence of two substances with the deprotonated molecule [M - H]- ion at m/z 299 and 459, respectively. Meanwhile, it was fully confirmed that B. uniformis participated in the catabolism of isorhamnetin glycoside and procyanidin B2. In the B. uniformis culture, kaempferol was synthesized through dihydroxylation of quercetin which could be catabolized into alphitonin by L. rhamnosus. Furthermore, LPP metabolites exerted to higher antioxidant activity than their precursors, and gave clues to understand interindividual difference for phenolic metabolism by gut microbiota.